Effects of underground coal mining disturbance on bacterial community diversity and its assembly processes - Fei Wang; Zehao Zhang; Zhaohua Lu; Junting Guo; Zhanyong Fu; Jingkuan Sun (PLoS ONE, 2025)
Vegetation restoration is an important indicator for evaluating the health of mining ecosystems. Soil microorganisms influence soil material cycling and play an important role in vegetation restoration. Clarifying the effects of mining on soil microbial communities has spleen benefits for vegetation restoration. In this study, we analyzed the effects of mine disturbance on soil bacterial communities by high-throughput sequencing and setting up sampling sites at different distances from the mine site. The results showed that the α-diversity of the bacterial community gradually increased and the β-diversity changed with increasing distance from the mine site. The changes in β-diversity were mainly from rare taxa. Distance increased the relative abundance of Actinobacteria, Acidobacteria, and Chloroflexi, but significantly decreased the relative abundance of Proteobacteria and Firmicutes. Bacterial networks within the mine had higher robustness and edge counts, and the robustness of molecular ecological networks decreased with increasing distance. To adapt to the nutrient-poor nature of mine soils, microbial populations preferred to cooperate with each other. The bacterial community assembly processes in all sample sites were dominated by random dispersal and heterogeneous selection, contributing 49.24% and 43.87%, respectively. The bacterial community assembly processes in the mining area were dominated by deterministic processes (heterogeneous selection, 69.4%). Salt, SUE and SOM had the greatest impact on total, rich and rare bacterial community α-diversity, which were significantly negatively, positively and positively correlated, respectively. TK, SOM, SUE and SALP had significant effects on the bacterial community structure of all three taxa. βNTI increased significantly with increasing differences in TN and ALSP and decreased with increasing differences in salt. The above results suggest that mining affects the diversity, composition, and assembling processes of bacterial communities, and that the effect on abundant and rare taxa are different.